2022
DOI: 10.1128/mbio.00433-22
|View full text |Cite
|
Sign up to set email alerts
|

The Leishmania donovani Ortholog of the Glycosylphosphatidylinositol Anchor Biosynthesis Cofactor PBN1 Is Essential for Host Infection

Abstract: Visceral leishmaniasis is a deadly infectious disease caused by the parasites Leishmania donovani and Leishmania infantum . It remains a major global health problem, and there is no licensed highly effective vaccine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 67 publications
1
3
0
Order By: Relevance
“…GPI-anchored lipophosphoglycans (LPG) and GP63 are recognized as potential virulence factors and required for transmission ( Isnard et al., 2012 ). Consistently, a recent study showed that the loss of GPI-anchored molecules in L. donovani , induced by the ablation of LdPBN1, an enzyme required for the GPI-anchor biosynthesis, lead to the failure of infection in mouse model of visceral leishmaniasis ( Roberts et al., 2022 ). The expressive predominance of GPI-anchored surface proteins indicates that the mechanisms for transport, targeting and sorting of proteins in kinetoplastids are divergent from mammalian cells, where the most surface molecules have transmembrane domains ( Manna et al, 2014 ).…”
Section: The First Order Er Functions In Trypanosomatidssupporting
confidence: 53%
See 1 more Smart Citation
“…GPI-anchored lipophosphoglycans (LPG) and GP63 are recognized as potential virulence factors and required for transmission ( Isnard et al., 2012 ). Consistently, a recent study showed that the loss of GPI-anchored molecules in L. donovani , induced by the ablation of LdPBN1, an enzyme required for the GPI-anchor biosynthesis, lead to the failure of infection in mouse model of visceral leishmaniasis ( Roberts et al., 2022 ). The expressive predominance of GPI-anchored surface proteins indicates that the mechanisms for transport, targeting and sorting of proteins in kinetoplastids are divergent from mammalian cells, where the most surface molecules have transmembrane domains ( Manna et al, 2014 ).…”
Section: The First Order Er Functions In Trypanosomatidssupporting
confidence: 53%
“…The protozoan Angomonas deanei, a trypanosomatid parasite of the gastrointestinal tract of insects, harbours a single endosymbiont in its cytoplasm. Recently, an elegant study by Catta-Preta and colleagues (2022), using FIB-SEM and proteomic analysis, showed a close association of symbiont bacteria with the ER, nucleus and, glycosomes of A. deanei. Multiple ER connections were found in dividing cells, mainly in the area of bacterial membrane constriction.…”
Section: The Third Order Function Of Er: Living With the Othersmentioning
confidence: 99%
“…In humans, the Leishmania major parasite, which is known to be causal for cutaneous Leishmaniasis, is commonly transmitted in west and middle Asia by sandflies of the genus Phlebotomus but also occurs in North and South America as well as in Europe [42]. The Leishmania donovani parasite causes visceral Leishmaniasis [43]. Chowdhury et al found that 3AC administration affected the production of TNF-α, IL-12, and interferon gamma (IFN-γ) positively, which the authors called anti-leishmanial cytokines, and reduced the production of IL-10 and TGF-β, called pro-leishmanial cytokines by the authors, as well as activated NO synthesis.…”
Section: Ac As a Ship1 Inhibitor In Leishmania Major And Leishmania D...mentioning
confidence: 99%
“…Following this discovery, more recent studies on attenuation have utilized CRISPR to generate null mutants with high efficiency. Among the deleted targets are Centrin1 [29,34,36,71], eukaryotic translation initiation factor 4E-1 (EIF4E1) [72] and the noncatalytic component of the GPImannosyltransferase (GPI-MTI) complex [73].…”
Section: Genetic Manipulation For Selecting Live-attenuated Leishmaniamentioning
confidence: 99%